The March and April 2023 ionospheric storms over Europe - Mošna, Zbyšek; Barta, Veronika; Berényi, Kitti Alexandra; Mielich, Jens; Verhulst, Tobias; Kouba, Daniel; Urbář, Jaroslav; Chum, Jaroslav; Koucká Knížová, Petra; Marew, Habtamu; Podolská, Kateřina; Bojilova, Rumiana (Frontiers in Astronomy and Space Sciences, 2024)
This paper presents a deep and comprehensive multi-instrumental analysis of two distinct ionospheric storms occurring in March and April 2023. We investigate the ionospheric response in the middle-latitudinal European region utilizing ionospheric vertical sounding at five European stations: Juliusruh, Dourbes, Pruhonice, Sopron, and a reference station, San Vito. Additionally, we employ Digisonde Drift Measurement, Continuous Doppler Sounding System, local geomagnetic measurements, and optical observations. We concentrate on the F2 and F1 region parameters and shape of the electron density profile. During the March event, a pre-storm enhancement was observed, characterized by an increase in electron density up to approximately 20% at northern stations, with minimal effect observed at San Vito. We present a novel detailed temporal and spatial description of a so-called G-condition. It was observed not only in the morning hours in the period of the increased geomagnetic activity during (and shortly after) the main phase of the storm, but also during low to moderate geomagnetic activity with Kp between 1 and 3+. Further, an alteration in the shape of the electron density profile, notably captured by the parameter B0 was observed. A substantial increase in B0, by several hundred percent, was noted during both events on the day of the geomagnetic disturbance and importantly also on the subsequent day with low-to-moderate geomagnetic activity. During both storms, the critical frequency foF1 decreased at all stations including San Vito. Changes in electron density in the F1 region indicate plasma outflow during morning hours. Distinct and persistent oblique reflections from the auroral oval were observed on the ionograms for several hours during both events and these observations were in agreement with optical observations of auroral activity and concurrent rapid geomagnetic changes at collocated stations. For the first time, we present a unique and convincing excellent agreement between the Continuous Doppler Sounding System and Digisonde Drift Measurement. The results reveal vertical movement of plasma up to ±80 m/s. Analysis of observed vertical plasma drifts and horizontal component H of magnetic field in Czechia and Belgium suggest that vertical motion of the F-region plasma is caused by ExB plasma drift.